Penambahan Umbi Bit Terhadap Karakteristik Sari Buah Apel - Alvin Yolanda Hidayatullah; Vonny Setiaries Johan; Yusmarini Yusmarini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
ABSTRACTThe purpose of this study was to obtain the additional effect of beetroot to the organoleptic content and nutrional manalagi apple juice. The research method used a completely randomized design with five treatments and three replications. The treatments consisted of AB1 (ratio of apple juice and beetroot juice 100:0), AB2 (ratio of apple juice and beetroot juice 90:10), AB3 (ratio of apple juice and beetroot juice 80:20), and AB4 (ratio of apple juice and beetroot juice 70:30) and AB5 (ratio of apple juice and beetroot juice 60:40). The data obtained were statistically analyzed using analysis of variance and continued with Duncan's New Multiple Range Test (DNMRT) at the 5% level. The results showed that combination of apple juice and beetroot juice significantly affected pH value, total dissolved solids and viscosity as well as color, aroma, taste and overall acceptance. The best treatment was AB3 (ratio of apple juice and beetroot juice 80:20). The product had pH value content 3.61, total dissolved solids 16.50 ˚brix, viscosity 1.402 cP, color 3.40 (red), 3.10 (aroma of apple and beetroot), taste 3.00 (taste of apple and beetroot) and overall rating with a score of 2.93 (rather like).Keywords:Apple juice, beetroot juice, juice